# TEST

## None:

``````# Please let:
⎣x = Math.log(x)
# Recall that Log and Exp are inverses:
⎣⎤x = x
# Define the unsquash function:
⎦x = Math.log(x / (1 - x))
⎦x = ⎣ x/(1-x)
# Show that unsquash is the inverse of squash:
⎦⎡x = ⎦ ⎡x
= ⎣ ⎡x/(1-⎡x)
= ⎣⎡x - ⎣ 1-⎡x
= ⎣ ⎤x/(⎤x+1) - ⎣ 1-⎡x
= ⎣⎤x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎤x/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ (⎤x+1-⎤x)/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ 1/(⎤x+1)
= x - ⎣ ⎤x+1 - (⎣1 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (0 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (-⎣ ⎤x+1)
= x - ⎣ ⎤x+1 + ⎣ ⎤x+1
= x
``````

## Fish:

``````# Please let:
⎣x = Math.log(x)
# Recall that Log and Exp are inverses:
⎣⎤x = x
# Define the unsquash function:
⎦x = Math.log(x / (1 - x))
⎦x = ⎣ x/(1-x)
# Show that unsquash is the inverse of squash:
⎦⎡x = ⎦ ⎡x
= ⎣ ⎡x/(1-⎡x)
= ⎣⎡x - ⎣ 1-⎡x
= ⎣ ⎤x/(⎤x+1) - ⎣ 1-⎡x
= ⎣⎤x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎤x/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ (⎤x+1-⎤x)/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ 1/(⎤x+1)
= x - ⎣ ⎤x+1 - (⎣1 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (0 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (-⎣ ⎤x+1)
= x - ⎣ ⎤x+1 + ⎣ ⎤x+1
= x
``````

## Ruby:

``````# Please let:
⎣x = Math.log(x)
# Recall that Log and Exp are inverses:
⎣⎤x = x
# Define the unsquash function:
⎦x = Math.log(x / (1 - x))
⎦x = ⎣ x/(1-x)
# Show that unsquash is the inverse of squash:
⎦⎡x = ⎦ ⎡x
= ⎣ ⎡x/(1-⎡x)
= ⎣⎡x - ⎣ 1-⎡x
= ⎣ ⎤x/(⎤x+1) - ⎣ 1-⎡x
= ⎣⎤x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎤x/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ (⎤x+1-⎤x)/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ 1/(⎤x+1)
= x - ⎣ ⎤x+1 - (⎣1 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (0 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (-⎣ ⎤x+1)
= x - ⎣ ⎤x+1 + ⎣ ⎤x+1
= x
``````

## Cucumber:

``````# Please let:
⎣x = Math.log(x)
# Recall that Log and Exp are inverses:
⎣⎤x = x
# Define the unsquash function:
⎦x = Math.log(x / (1 - x))
⎦x = ⎣ x/(1-x)
# Show that unsquash is the inverse of squash:
⎦⎡x = ⎦ ⎡x
= ⎣ ⎡x/(1-⎡x)
= ⎣⎡x - ⎣ 1-⎡x
= ⎣ ⎤x/(⎤x+1) - ⎣ 1-⎡x
= ⎣⎤x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎤x/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ (⎤x+1-⎤x)/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ 1/(⎤x+1)
= x - ⎣ ⎤x+1 - (⎣1 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (0 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (-⎣ ⎤x+1)
= x - ⎣ ⎤x+1 + ⎣ ⎤x+1
= x
``````

## Coffee:

``````# Please let:
⎣x = Math.log(x)
# Recall that Log and Exp are inverses:
⎣⎤x = x
# Define the unsquash function:
⎦x = Math.log(x / (1 - x))
⎦x = ⎣ x/(1-x)
# Show that unsquash is the inverse of squash:
⎦⎡x = ⎦ ⎡x
= ⎣ ⎡x/(1-⎡x)
= ⎣⎡x - ⎣ 1-⎡x
= ⎣ ⎤x/(⎤x+1) - ⎣ 1-⎡x
= ⎣⎤x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎤x/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ (⎤x+1-⎤x)/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ 1/(⎤x+1)
= x - ⎣ ⎤x+1 - (⎣1 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (0 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (-⎣ ⎤x+1)
= x - ⎣ ⎤x+1 + ⎣ ⎤x+1
= x
``````

## GnuPlot:

``````# Please let:
⎣x = Math.log(x)
# Recall that Log and Exp are inverses:
⎣⎤x = x
# Define the unsquash function:
⎦x = Math.log(x / (1 - x))
⎦x = ⎣ x/(1-x)
# Show that unsquash is the inverse of squash:
⎦⎡x = ⎦ ⎡x
= ⎣ ⎡x/(1-⎡x)
= ⎣⎡x - ⎣ 1-⎡x
= ⎣ ⎤x/(⎤x+1) - ⎣ 1-⎡x
= ⎣⎤x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎤x/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ (⎤x+1-⎤x)/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ 1/(⎤x+1)
= x - ⎣ ⎤x+1 - (⎣1 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (0 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (-⎣ ⎤x+1)
= x - ⎣ ⎤x+1 + ⎣ ⎤x+1
= x
``````

``````# Please let:
⎣x = Math.log(x)
# Recall that Log and Exp are inverses:
⎣⎤x = x
# Define the unsquash function:
⎦x = Math.log(x / (1 - x))
⎦x = ⎣ x/(1-x)
# Show that unsquash is the inverse of squash:
⎦⎡x = ⎦ ⎡x
= ⎣ ⎡x/(1-⎡x)
= ⎣⎡x - ⎣ 1-⎡x
= ⎣ ⎤x/(⎤x+1) - ⎣ 1-⎡x
= ⎣⎤x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎤x/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ (⎤x+1-⎤x)/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ 1/(⎤x+1)
= x - ⎣ ⎤x+1 - (⎣1 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (0 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (-⎣ ⎤x+1)
= x - ⎣ ⎤x+1 + ⎣ ⎤x+1
= x
``````

## R:

``````# Please let:
⎣x = Math.log(x)
# Recall that Log and Exp are inverses:
⎣⎤x = x
# Define the unsquash function:
⎦x = Math.log(x / (1 - x))
⎦x = ⎣ x/(1-x)
# Show that unsquash is the inverse of squash:
⎦⎡x = ⎦ ⎡x
= ⎣ ⎡x/(1-⎡x)
= ⎣⎡x - ⎣ 1-⎡x
= ⎣ ⎤x/(⎤x+1) - ⎣ 1-⎡x
= ⎣⎤x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎤x/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ (⎤x+1-⎤x)/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ 1/(⎤x+1)
= x - ⎣ ⎤x+1 - (⎣1 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (0 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (-⎣ ⎤x+1)
= x - ⎣ ⎤x+1 + ⎣ ⎤x+1
= x
``````

## Yaml:

``````# Please let:
⎣x = Math.log(x)
# Recall that Log and Exp are inverses:
⎣⎤x = x
# Define the unsquash function:
⎦x = Math.log(x / (1 - x))
⎦x = ⎣ x/(1-x)
# Show that unsquash is the inverse of squash:
⎦⎡x = ⎦ ⎡x
= ⎣ ⎡x/(1-⎡x)
= ⎣⎡x - ⎣ 1-⎡x
= ⎣ ⎤x/(⎤x+1) - ⎣ 1-⎡x
= ⎣⎤x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎤x/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ (⎤x+1-⎤x)/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ 1/(⎤x+1)
= x - ⎣ ⎤x+1 - (⎣1 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (0 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (-⎣ ⎤x+1)
= x - ⎣ ⎤x+1 + ⎣ ⎤x+1
= x
``````

## TCL:

``````# Please let:
⎣x = Math.log(x)
# Recall that Log and Exp are inverses:
⎣⎤x = x
# Define the unsquash function:
⎦x = Math.log(x / (1 - x))
⎦x = ⎣ x/(1-x)
# Show that unsquash is the inverse of squash:
⎦⎡x = ⎦ ⎡x
= ⎣ ⎡x/(1-⎡x)
= ⎣⎡x - ⎣ 1-⎡x
= ⎣ ⎤x/(⎤x+1) - ⎣ 1-⎡x
= ⎣⎤x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎡x
= x - ⎣ ⎤x+1 - ⎣ 1-⎤x/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ (⎤x+1-⎤x)/(⎤x+1)
= x - ⎣ ⎤x+1 - ⎣ 1/(⎤x+1)
= x - ⎣ ⎤x+1 - (⎣1 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (0 - ⎣ ⎤x+1)
= x - ⎣ ⎤x+1 - (-⎣ ⎤x+1)
= x - ⎣ ⎤x+1 + ⎣ ⎤x+1
= x
``````